Upaya Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Membaca Al-Qur’an Siswa SMA - Rizca Hidayah Seftya; Al Ikhlas (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The problem of this research is that there are still many students who have difficulty in reading the Qur'an, seeing this problem the emergence of efforts from PAI teachers on how to overcome difficulties in reading the Qur'an in class XI students at SMA Negeri 1 Sawahlunto. This study aims to determine the efforts made by PAI teachers in overcoming difficulties in reading the Qur'an of class XI students at SMA Negeri 1 and to find out the inhibiting and supporting factors of PAI teachers in overcoming difficulties in reading the Koran at SMA Negeri 1 Sawahlunto. This type of research is field research and the method used is qualitative research methods. The results of the research are the first, the efforts of PAI teachers in overcoming difficulties in reading the Qur'an, namely 1) peer tutoring, 2) using drill and iqro methods, 3) face to face, 4) coming to the place megaji, 5) holding special hours, 6) tahsin teachers, 7) calling parents. Second, the inhibiting and supporting factors are the existence of internal and external factors, while the supporting factors are from the internet such as YouTube or other applications, radio, and Islamic television which discuss how to read the Qur'an.